(untitled) (Bangladesh Journal of Botany, 2020)
This experiment was undertaken to depict the favourable condition for mycelial growth, molecular identification and phylogenetic relationship of the selected strains of Pleurotus salmoneostramineus. Suitable temperature and pH were obtained at 25ºC and 6, respectively. Mushroom complete, glucose peptone and yeast malt extract culture media were favorable, while Hennerberg and Hoppkins were unfavorable. Dextrin was the best and xylose was the less effective carbon sources. Inorganic nitrogen sources were less effective for the mycelial growth of P. salmoneostramineus. The sequences of internal transcribed spacer (ITS) region of selected strains revealed that the total length ranged from 614 to 663 bp. The size of the ITS1 and ITS2 regions varied among the strains. Sequence analysis showed that 5.8S of rDNA sequences were identical. Phylogenetic tree of the ITS region sequences indicated that strains of P. salmoneostramineus belong to same cluster. The reciprocal homologies of the ITS region sequences ranged from 98 to 100%. The strains of P. salmoneostramineus were also analyzed by random amplification of polymorphic DNA (RAPD) with 20 arbitrary primers. RAPD results suggested that tested strains of P. salmoneostramineus were genetically similar with some variations, thus it could be concluded that RAPD and ITS techniques were well competent for detecting the genetic diversity of all tested strains of P. salmoneostramineus.